f(

f(s(

R

↳Dependency Pair Analysis

F(x,y) -> F(x,x)

F(s(x),y) -> F(y,x)

Furthermore,

R

↳DPs

→DP Problem 1

↳Usable Rules (Innermost)

**F(s( x), y) -> F(y, x)**

f(x,y) -> f(x,x)

f(s(x),y) -> f(y,x)

innermost

As we are in the innermost case, we can delete all 2 non-usable-rules.

R

↳DPs

→DP Problem 1

↳UsableRules

→DP Problem 2

↳Non Termination

**F(s( x), y) -> F(y, x)**

none

innermost

Found an infinite P-chain over R:

P =

F(s(x),y) -> F(y,x)

F(x,y) -> F(x,x)

R = none

s = F(

evaluates to t =F(

Thus, s starts an infinite chain.

Duration:

0:00 minutes